دراسة المضاعفات القريبة لجراحة الغدة الدرقية - علي ماجد; قنجراوي أكثم; مانجيان توماس (Latakia University Journal -Medical Sciences Series, 2016)
أجريت الدراسة على (73) مريضا أجري لهم عمل جراحي على الدرق في مشفى الأسد الجامعي في اللاذقية بين عامي 2012_ 2014 . حيث قسمت الدراسة إلى: استرجاعية (32 مريضاً ) دراسة استقبالية ( 41 مريضاً ) وخضع (11) مريضا منهم لعمل جراحي ثان بسبب وجود خباثة بنسبة (16,66%) . كان الاستئصال التام في الجهتين هو التداخل الأكثر شيوعا" بنسبة (57.14%) يليه استئصال فص تام مع برزخ (28.79 %) . نسبة المضاعفات القريبة الكلية (11.9%) وقد كان التكزز هو المضاعفة الأكثر تكرارا من المضاعفات بنسبة (3,57%) يليه إصابة العصب الحنجري الراجع والحنجري العلوي والنزف بنسبة (2,38 %) لكل منها. حصلت النسبة الأعلى من المضاعفات في العمليات البدئية في عمليات الاستئصال التام البدئي يليه استئصال تام بجهة. جراحة الدرق الناكسة تحمل خطورة مضاعفات أكثر من المداخلات البدئية . The Research has been made on (73) patients for whom a surgical operation was made on the thyroid in Al-Assad University Hospital in Lattakia in 2000-2007. The study was divided into: retrospective (32patients), prospective (41patients) and (11) patients of were subjected to second operation due to existence of a malignant cancer with a percentage of (16,66%) . The Total Thyroidectomy on both side was the most spread intervention with a percentage of (57,14%) and next to it was the thyroid lobectomy with a percentage of (28,79%). The percentage of Total Early complication is (11,9%) and the Tetania was the most repeated complication with a percentage of (3,57%) and next to it was the Recurrent laryngeal nerve ,the Superior laryngeal nerve and the bleeding with a percentage of (2,38%)for each . The higher percentage of complication has occurred in the starting operation of the Total Thyroidectomy and next to it the Thyroid lobectomy . The surgery of the Relapsed Thyroid is subject to more dangerous complications from the starting intervention .